Figure 2. Paranaitis wahlbergi, A in A revision of Paranaitis Southern, 1914 (Polychaeta: Phyllodocidae) - Kato, Tetsuya; Pleijel, Fredrik (Zenodo, 2003)
Figure 2. Paranaitis wahlbergi, A, specimen from Greenland (ZMUC-POL-1500). B–E, specimen from Norway (SMNH- 22502). A, anterior end of large specimen, with partly everted proboscis, dorsal view. B, anterior end of small specimen, dorsal view. C, parapodium of segment 14, anterior view. D, parapodium of segment 33, posterior view. E, same, anterior view. : Published as part of Kato, Tetsuya & Pleijel, Fredrik, 2003, A revision of Paranaitis Southern, 1914 (Polychaeta: Phyllodocidae), pp. 379-429 in Zoological Journal of the Linnean Society 138 (4) on page 387, DOI: 10.1046/j.1096-3642.2003.00069.x, http://zenodo.org/record/5437920